THE POSITION OF AN APOSTASY WIFE AS A CAUSE FOR THE DISSOLUTION OF A MARRIAGE IN THE COMPILATION OF ISLAMIC LAW AND ITS IMPLICATIONS FOR POST-DIVORCE RIGHTS - Alhadi Saputra; Hanif Nur Widhiyanti; Nur Chanifah (CV. RADJA PUBLIKA, 2025)
Conversion to religion (apostasy) in Islamic marriage is a complex phenomenon that gives rise to debate between legal norms and social reality. In the context of Indonesian national law, apostasy has not been explicitly regulated in Law Number 1 of 1974 concerning Marriage. This legal gap is filled by the Compilation of Islamic Law (KHI), which, in Article 116 letter (h), stipulates that conversion to religion or apostasy can be grounds for divorce. However, in religious court practice, there is a disparity in decisions between courts that interpret apostasy as grounds for fasakh (annulment) and those that interpret it as grounds for divorce (talaq). This disparity has legal implications for women's rights after divorce, particularly regarding the right to maintenance during the iddah period, mut'ah, maskan, and kiswah. This study aims to explain the position of a wife who apostatizes as a cause of marital dissolution from the perspective of the Compilation of Islamic Law (KHI) and analyze its legal consequences for post-divorce rights. The method used is normative legal research with a statutory, conceptual, and analytical approach. The results of the study indicate that a wife who apostatizes causes the marriage contract to be annulled (fasakh), but in practice, religious courts often still process it through the divorce mechanism (divorce talak) to ensure orderly legal administration. This disparity impacts the different treatment of the rights of apostate wives. From the perspective of legal utility, judges should consider the value of substantive justice and protection for women, even if the woman concerned has left Islam.